Influences of price, quality of food and customer services towards customer satisfaction:a case study of cafe2u in Taman Bendahara, Pengkalan Chepa. - Nur Hidayah Ismail, . (2012)
The customer play an important part to measure satisfaction after eats at restaurant. Owners of the restaurant should be increased the productivity to make sure that their restaurant can be more attractive and clean. This study is examined the customer satisfaction level towards Cafe2u Taman Bendahara, Pengkalan Chepa. The main objectives of this study were to examine the relationship between price, quality of food, customer’s service and customer satisfaction level at Cafe2u. The independent variables included in this research are price, quality of food, customer services and customer satisfaction level as dependent variable. A survey questionnaire which consists of three parts to measure demographic factors, independent variable and dependent variable was constructed based on past research. A total of 110 respondents from Universiti Malaysia Kelantan were selected as a sample. Data collected was analyzed using PASW Statistic 18.0. From the findings, there are positive correlation relationships between price, quality of food and customer services with customer satisfaction level. New findings were discovered after conducting this research. Future researcher could discover the reason for those factors is becoming the leading factors in determining customer satisfaction in this field. Discussion on findings, conclusion and limitation of study are also included in the report.